A Case Study: Majujaya Bank Berhad - Loh, Chuan Seng (1997)

(untitled)
This purpose of this case study is to appreciate the application of strategic planning tools to facilitate the realisation of the objectives of Custodial Service Department of Majujaya Bank Berhad. Part 1 of this case has discussed the development of Majujaya Bank Berhad during the eighties whereby it was linked to the banking group from Sweden which owned thitty percents of the bank. The association had provided synergy to the bank whereby through the formation of Custodial Services Department, Majujaya Bank Berhad was able to capitalise on the investment arm of the Swedish partner to generate fees based income arising from trading and investment activities on the Kuala Lumpur Stock Exchange. Due t.o the relatively small clientele base, the department was vulnerable when the Swedish partner being the largest customer left the department as a result of changes in ownership within the Swedish banking group. Realising the various internal as well as external factors, the department head was working on plan to overcome the predicament in order to meet all objectives of the department and the bank. Part 2 of the case study has analysed the various factors by using the strategic tools namely SWOT as well as SPACE models and concluded that the most appropriate option for Custodial Services Department is to expand the business into the regional markets via working with fund managers who invest in regional markets. In order to proceed with regionalisation, the department needs to increase its efficiency and effectiveness by streamlining its operation and expand the capability of the computer systems while at the same time marketing its services to secure more customers. It is through this approach at moderate scale that the department would be able to meet its objectives of being a leading local as well as regional provider while at the same time contributing to the bank's objective of achieving tier 1 by 1998.